Early detection of type 2 diabetes in socioeconomically disadvantaged areas in Stockholm - comparing reach of community and facility-based screening - Linda Timm; Katri Harcke; Ida Karlsson; Kristi Sidney Annerstedt; Helle Mölsted Alvesson; Nouha Saleh Stattin; Birger C Forsberg; Claes-Göran Östenson; Meena Daivadanam (Taylor & Francis Group, 2020)
Background Type 2 diabetes and its high-risk stage, prediabetes, are often undiagnosed. Early detection of these conditions is of importance to avoid organ complications due to the metabolic disturbances associated with diabetes. Diabetes screening can detect persons unaware of diabetes risk and the elevated glucose levels can potentially be reversed through lifestyle modification and medication. There are mainly two approaches to diabetes screening: opportunistic facility-based screening at health facilities and community screening. Objective To determine the difference in population reach and participant characteristics between community- and facility-based screening for detection of type 2 diabetes and persons at high risk of developing diabetes. Methods Finnish diabetes risk score (FINDRISC) is a risk assessment tool used by two diabetes projects to conduct community- and facility-based screenings in disadvantaged suburbs of Stockholm. In this study, descriptive and limited inferential statistics were carried out analyzing data from 2,564 FINDRISC forms from four study areas. Community- and facility-based screening was compared in terms of participant characteristics and with population data from the respective areas to determine their reach. Results Our study found that persons born in Africa and Asia were reached through community screening to a higher extent than with facility-based screening, while persons born in Sweden and other European countries were reached more often by facility-based screening. Also, younger persons were reached more frequently through community screening compared with facility-based screening. Both types of screening reached more women than men. Conclusion Community-based screening and facility-based screening were complementary methods in reaching different population groups at high risk of developing type 2 diabetes. Community screening in particular reached more hard-to-reach groups with unfavorable risk profiles, making it a critical strategy for T2D prevention. More men should be recruited to intervention studies and screening initiatives to achieve a gender balance.